Biofabricated platinum nanoparticles: therapeutic evaluation as a potential nanodrug against breast cancer cells and drug-resistant bacteria. Issue 40 (16th July 2021) - Manzoor, Saliha; Bashir, Dar Junaid; Imtiyaz, Khalid; Rizvi, M. Moshahid A.; Ahamad, Irshad; Fatma, Tasneem; Agarwal, Nidhi Bharal; Arora, Indu; Samim, Mohammed
Abstract : The present study involves the green synthesis of platinum nanoparticles and their application as anticancer and antibacterial agents. Abstract : Use of plant extracts for the synthesis of various metal nanoparticles has gained much importance recently because it is a simple, less hazardous, conservative and cost-effective method. In this research work, platinum nanoparticles were synthesized by treating platinum ions with the leaf extract of Psidium guajava and their structural properties were studied using various characterization techniques. The formation of platinum nanoparticles was confirmed by the disappearance of the absorbance peak at 261 nm in UV-visible spectra. The results of gas chromatography-mass spectrometry (GC-MS) and Fourier transform infrared spectroscopy (FT-IR) analysis showed functional moieties responsible for bio-reduction of metal ions and stabilization of platinum nanoparticles. The use of dynamic light scattering (DLS) imaging techniques confirmed the formation of stable monodispersed platinum nanoparticles showing a zeta potential of −23.4 mV. The morphological examination using high resolution transmission electron microscopy (HR-TEM) and Scanning electron microscopy (SEM) confirmed the formation of spherical platinum nanoparticles with an average diameter of 113.2 nm. X-ray powder diffraction (XRD) techniques showed the crystalline nature of biosynthesized platinum nanoparticles with a face-centered cubic structure. The results of energy-dispersive X-ray spectroscopy (EDAX) showed 100% platinum content by weight confirming the purity of the sample. The cytotoxic effect of biosynthesized platinum nanoparticles assessed in a breast cancer (MCF-7) cell-line by a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, revealed an IC50 of 167.2 μg ml −1 . The results of a wound healing assay showed that treatment with platinum nanoparticles induced an anti-migratory effect on MCF-7 cells. In the cell cycle phase distribution, treatment with platinum nanoparticles inhibited cell proliferation as determined by flow cytometry with PI staining. Significant cell cycle arrest was detected at the G0/G1 phase with a notable decrease in the distribution of cells in the S and G2/M phases. The anti-bacterial activity of bio-synthesized platinum nanoparticles was evaluated against four pathogenic bacteria i.e. B. cereus (Gram positive), P. aeruginosa (Gram negative), K. pneumonia (Gram negative) and E. coli (Gram negative). The biosynthesized platinum nanoparticles were found to show dose-dependent inhibition against pathogenic bacteria with a significant effect on Gram-negative bacteria compared to Gram-positive bacteria. This synergistic blend of green and simplistic synthesis coupled with anti-proliferative and anti-bacterial properties makes these biogenic nanoparticles suitable in nanomedicine.